Valproic acid induced necrohemorragic pancreatitis: Case report and diagnostic approach in uncommon pancreatitis. (2019) - Barbosa, Silvia Carolina; Cabrera, Paulo; Guerra, Bayron; Roman, Carlos F.
Highlights: Is convenient to consider a medication induced necrohemorragic pancreatitis in patients without clear causative agent. Because progressive increase in AP incidence and the impact on morbidity and mortality is crucial determine an etiologic diagnosis in order to proceed to appropriate therapeutic interventions as for recurrence prevention. The valproic acid is a strong AP inducer (class Ia) in its evidence based classification and review of literature on medication induced AP, with the biomolecular evidence of pancreatic injury. An adequate initial approach with a complete clinical history and pharmacological background, good physical examination, and pertinent extension of laboratory tests are necessary in order to achieve a proper AP etiology. The etiologic diagnosis algorithm for AP proposed could be considered as a diagnostic exclusion tool, and is easy to apply for a timely therapeutic approach in medication induced AP. Abstract: Background: Acute pancreatitis (AP) is one of the most frequent gastrointestinal alterations in the United States. Medication induced AP has been undervalued in the surgical environment as etiologic entity of necrohemorragic pancreatitis (NHP). A case of NHP induced by valproic acid (VA) is presented, and an exclusion diagnostic algorithm is proposed. Case report: A 29-year-old female with past medical history of migraine controlled with VA was admitted to our institute for acute abdominal pain and peritoneal irritation. An exploratory laparotomy was performed, finding pancreatic necrosis and a diagnosis of NHP was determined. The most frequent etiologies for AP were discarded. An exclusion diagnostic algorithm was performed reaching VA as etiologic gent. The treatment consisted on medication withdrawal, oral restriction, parenteral nutrition, hydration, analgesia and peritoneal wash-outs with a positive outcome. Conclusion: Is convenient to consider a medication induced AP in patients without clear causative agent, such as the VA case presented. An etiological diagnosis algorithm of exclusion is proposed, for an adequate therapeutic approach in medication induced PNH. Algorithm validation is required.